Pharmacokinetics, Tissue Distribution, and Excretion of Salidroside in Rats - Zhang, Ying; Li, Liqun; Lin, Li; Liu, Jianxun; Zhang, Zaohua; Xu, Dongjin; Xiang, Feijun (Planta Medica, 2013)
The present study investigated the pharmacokinetics, excretion, and tissue distribution of salidroside, a main active constituent in the roots of Rhodiola species. The plasma concentration declined rapidly following the intravenous dosing at 7.5, 15, and 30 mg/kg with a short half-life time of about 1 h. The mean values of area under the concentration-time curve (300.48 ± 36.73, 514.51 ± 134.99, and 1036.64 ± 101.67 mg · min/L), total body clearance (0.025 ± 0.003, 0.031 ± 0.008, and 0.029 ± 0.003 L/min/kg), and distribution value (2.02 ± 0.80, 2.47 ± 1.09 and 2.58 ± 0.68 L/kg) suggested linear pharmacokinetics between the three doses. After intravenous injection of salidroside at 15 mg/kg, the total cumulative recovery of salidroside in urine was 53.67 ± 12.03 % over 48 h, but only 0.09 ± 0.03 % and 0.18 ± 0.18 % of the dosage was excreted in bile and feces. Concentrations of salidroside in 12 tissues as well as plasma were evaluated at 15, 40, and 120 min after dosing. At all time points, no higher concentration of salidroside was detected in tissues than that in plasma, with the lowest concentration of salidroside being observed in the brain, liver, fat, and skeletal muscle were tissues with a higher concentration of salidroside. A better distribution was also observed in the ovary and testis than that in the kidney and spleen. This finding demonstrated that salidroside is eliminated from plasma rapidly mainly by kidney clearance and conspicuously penetrated well into the skeletal muscle, fat, ovary and testis. A total recovered salidroside of about 54 % from excretion routes suggested that the metabolism was likely to take an important role in its elimination.
Keywords: salidroside; pharmacokinetics; excretion; distribution; HPLC-UV; LC-MS/MS; Rhodiola; Crassulaceae